The Role of Schools in Literacy in Elementary Schools - Putra, M. Jaya adi; Azmi, Aldila Ulul; Sari , Anugerah Permata; Ningtias, Legia Ayu; Mismeidi, Mismeidi; Setiowati, Rilda (PT FORMOSA CENDEKIA GLOBAL, 2023)
Literacy is closely related to an individual's ability to read, write, speak and understand information and solve daily life problems. The current literacy level of students is at a low level because there is still a lack of students being asked to read. Interest in reading is the desire and encouragement of students to like and enjoy reading activities. Based on the aim of this research, namely to determine the role of schools in literacy, this research uses descriptive qualitative research with data collection techniques through observation, interviews and documentation. The object of this research is SDN 194 Pekanbaru. In this research, three indicators were tested, namely the provision of infrastructure, the provision of school library programs and services. From these three indicators, the results showed that the role of school literacy has a fairly good average in improving students' literacy skills. From the results of observations made by researchers, it was found that the role of schools in literacy is to provide facilities and infrastructure for literacy at SDN 194 Pekanbaru, such as providing book reading corners in class, wall magazines, reading corners, posters with motivational words in class and also providing literacy programs such as: reading 30 before learning begins, a reading journal program which at the end of the semester, the best students will be given rewards and SDN 194 Pekanbaru also provides a library.